2018
DOI: 10.1063/1.5038174
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substrate interactions on the glass transition and length-scale of correlated dynamics in ultra-thin molecular glass films

Abstract: Interfacial interactions can play an important role in the glass transition temperature (Tg) and relaxation dynamics of ultra-thin glass polymer films. We have recently shown that similar to the polymeric systems in ultra-thin molecular glass films of N, N′-Bis(3-methylphenyl)-N, N′-diphenylbenzidine (TPD), the Tg is reduced and dynamics are enhanced. Furthermore, in molecular glass systems, as the film thickness is reduced below ∼30 nm, the dynamics at the two interfaces correlate such that the range of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 58 publications
3
25
0
Order By: Relevance
“…2A for the lowest temperature simulated, the relaxation time everywhere in a 4 σ film is less than the relaxation time at the surface of a 26 σ film. This provides an explanation for another puzzling experimental study in which the ellipsometric T g of very thin films was reported to be smaller than the low-temperature onset of the glass transition in a thick film (15), interpreted as the free-surface T g .…”
Section: Simulation Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…2A for the lowest temperature simulated, the relaxation time everywhere in a 4 σ film is less than the relaxation time at the surface of a 26 σ film. This provides an explanation for another puzzling experimental study in which the ellipsometric T g of very thin films was reported to be smaller than the low-temperature onset of the glass transition in a thick film (15), interpreted as the free-surface T g .…”
Section: Simulation Resultsmentioning
confidence: 65%
“…1). For relatively thick films where gradient effects are dominant, superposition of the nearly exponential thick-film barrier gradient can explain, to leading order, gradient flattening (60) and speed up of relaxation beyond the bulk film surface in thin films (15). However, with decreasing thickness, finite size confinement effects ultimately emerge due to the coupling of the consequences of two interfaces on the longer-range collective elasticity effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is conceivable that having a distinct surface and bulk Tg that converge to a single value upon reduction of h would lead to a narrowing of the glass transition, this view does not agree with results in supported thin films with weak substrate interactions. In these cases, the reduction of ∇Tg is accompanied by a broadening of Tg for both polymeric and molecular glass films, suggesting the material still samples a broad distribution of dynamics in ultrathin films (9,10). This transition occurs in two stages.…”
mentioning
confidence: 95%
“…As such, the degree of enhanced surface mobility and mobility gradients are critical factors in the formation of stable glasses (3,11,17,18). While the effect of film thickness on the surface mobility and gradients of liquid-quenched (LQ) glasses has been studied in the past (19,20), there are limited data on the role of film thickness in the stability of vapor-deposited glasses. In vapor-deposited toluene, it has been shown that decreasing the film thickness from 70 to 5 nm can increase the thermodynamic stability but decrease the apparent kinetic stability (5,6).…”
mentioning
confidence: 99%